2007
DOI: 10.1086/521293
|View full text |Cite
|
Sign up to set email alerts
|

Combining Strong and Weak Gravitational Lensing in Abell 1689

Abstract: We present a reconstruction of the mass distribution of galaxy cluster Abell 1689 at z = 0.18 using detected strong lensing features from deep HST/ACS observations and extensive ground based spectroscopy. Earlier analyses have reported up to 32 multiply imaged systems in this cluster, of which only 3 were spectroscopically confirmed. In this work, we present a parametric strong lensing mass reconstruction using 24 multiply imaged systems with newly determined spectroscopic redshifts, which is a major step forw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

54
520
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(579 citation statements)
references
References 69 publications
54
520
0
1
Order By: Relevance
“…We also note that photometric redshifts based on upto five photometric bands are becoming more common as a method for selecting background galaxies (Limousin et al 2007; Gavazzi et al 2009;Gruen et al 2013;Applegate et al 2014;McCleary, dell'Antonio & Huwe 2015;Melchior et al 2015). However photometric redshifts based on a small number of filters are problematic for galaxies with blue observed colours because their spectral energy distribution is relatively featureless.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We also note that photometric redshifts based on upto five photometric bands are becoming more common as a method for selecting background galaxies (Limousin et al 2007; Gavazzi et al 2009;Gruen et al 2013;Applegate et al 2014;McCleary, dell'Antonio & Huwe 2015;Melchior et al 2015). However photometric redshifts based on a small number of filters are problematic for galaxies with blue observed colours because their spectral energy distribution is relatively featureless.…”
Section: Introductionmentioning
confidence: 92%
“…Broadhurst et al 2005;Limousin et al 2007). It is therefore of prime importance to make a secure selection of background galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…A1689 (z = 0.183) has the largest Einstein radius of all massive lensing clusters, θ E ∼ 50 . Broadhurst et al (2005) and Limousin et al (2007) performed a strong lensing analysis using HST data and identified 115 images of 34 multiply lensed background galaxies in the redshift range 1 < z < 5.5 based on spectroscopic and photometric redshift estimates. A cluster mass model of AC114 (z = 0.312, θ E ∼ 30 ) and several strongly lensed sources, including a 5-image configuration at z = 3.347 were presented in Campusano et al (2001).…”
Section: Clusters As Gravitational Telescopesmentioning
confidence: 99%
“…In particular, dwarfs and low surface-brightness galaxies suggest a much shallower profile with a relatively flat slope (α ≥ −0.5 with ρ(r) ∼ r α ) (Palunas & Williams 2000;Salucci & Burkert 2000;de Blok et al 2001;Swaters et al 2003;Gentile et al 2004;Spekkens et al 2005;Goerdt et al 2006;Walter et al 2008;Oh et al 2011;Walker & Peñarrubia 2011). On the other extreme of the halo mass scale, galaxy clusters tend to have a central cusp, as evidenced by studies combining strong and weak lensing (e.g., Limousin et al 2007;Leonard et al 2007; Umetsu et al 2007), but shallower slopes than the NFW one can also be found within the inner ≈ 5 kpc (Sand et al 2004;Sand et al 2008;Newman et al 2009;Newman et al 2011;Newman et al 2013;Richtler et al 2011). Note that a recent study found a cusp slope over 5 − 350 kpc of α = −1.62, again from combined weak and strong lensing analysis of the complete CLASH cluster sample (Zitrin et al 2015).…”
Section: Introductionmentioning
confidence: 98%